GE_GERICHTE C/10104/2015 vom 12. Oktober 2015 - GE Cour de justice (2015)
BAIL À LOYER; ÉVACUATION(EN GÉNÉRAL); PAIEMENT DE L'ARRIÉRÉ; DROIT D'ÊTRE ENTENDU; INTERPRÈTE | CPC.319.a; CPC.321.1; Cst.29.2; CPC.53; LaCC.30.4